INFLUENCE OF VAISNAVISM ON THE MISING COMMUNITY OF ASSAM - Pegu, Popy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Mising, officially known as Miri, is the second largest tribal group in Assam. Originally, they lived in the hills, particularly in the Siang valley of Arunachal Pradesh, but around the 13th century A.D., they migrated to the plains of Assam. It has been seen that the traditional beliefs and practices of the Mising community have undergone significant changes over time. Among these changes, the influence of Vaisnavism stands out as particularly prominent. over the time, the Kal Sanghati, a group of Vaisnavism become popular among the Misings. On the basis of nature of practices, it divided the misings into two groups- Bhagavatia and Kewalia.